Restauración de voz deteríorada por ruido de pulsos - Brito Collantes, Jorge (2010)
Audio signals are susceptible to pulse noise in many cases such as electromagnetic interference in mobile systems, poor synchronization in digital recording or even scratch noise of an old LP record to name a few. A number of software packages for noise cancellation have been developed but they are expensive and use complex algorithms. This paper presents an adaptive method for suppressing pulse noise specifically from voice signals. Pulses are removed by selectively applying median filtering to contaminated signal regions only, avoiding high frequency losses in the undamaged sections.